Design and Tuning of Reduced Order H-Infinity Feedforward Compensators for Active Vibration Control - Alma, M.; Martinez, J. J.; Landau, I. D.; Buche, G. (IEEE transactions on control systems technology, 2012)
This brief presents a procedure for design and tuning of reduced orders H ∞ feedforward compensators for active vibration control systems subject to wide band disturbances. The procedure takes in account the inherent "positive" feedback coupling between the compensator system and the measurement of the image of the disturbance. It also takes advantage of the availability of reliable models obtained by system identification. A controller order reduction technique is proposed for reducing the complexity of the nominal H ∞ controller without degrading the performance. Experimental results obtained on an active vibration control system for a flexible mechanical structure will illustrate the procedure.